Prefeasibility mining studies by using electrical resistivity imaging (ERI) in Keratong, Pahang - Puteri Izrina, Ismi; Mohd Fakhrurrazi, Ishak; Solahuddin, Daud (Geological Society of Malaysia, 2025)
The allure of hidden mineral wealth has long driven exploration yet the complexity of uncovering these resources beneath layers of the earth’s surface remains a formidable challenge. In Keratong, Pahang, a geophysical investigation employing electrical resistivity imaging (ERI) was conducted to map the intricate subsurface landscape across a 1.25 km² of a study area. Eight survey lines were meticulously analysed using a combination of resistivity and induced polarization techniques thus culminating in vivid 2D pseudo-sections and a dynamic 3D contour model. These visualisations reveal a stratified geological profile comprising of overburdened soil, weathered metasediments, and fractured sedimentary rocks that obscure the presence of potential metallic mineral deposits. Notably, zone exhibiting low resistivity (0–40 Ωm) and high chargeability (>240 ms) suggest the presence of mineralization at depths ranging from 5 to 20 meters, particularly along Line 2, 4, 5, 6, 7, and 8. The northwest region, identified as suitable for tailing ponds, mine facilities, and stable terrain near Line 1 and 3 is recommended for stockpiling while demonstrating an integrated approach for exploration and sustainable site planning. This research underscores the transformative potential of ERI in both location subsurface mineral resources and stating the design efficiency for environmentally responsible mining operations.